Electrical resistivity tomography to detect the effects of tillage in a soil with a variable rock fragment content. (18th February 2013) - Rossi, R.; Amato, M.; Pollice, A.; Bitella, G.; Gomes, J. J.; Bochicchio, R.; Baronti, S.
Summary Electrical resistivity tomography (ERT) is a promising non‐destructive tool to characterize agricultural soils where management effects are superimposed on natural variability. The aim of our study was to test whether ERT was capable of detecting stones and tillage effects in a soil with a variable rock fragment content. Field experiments were conducted by performing a set of three two‐dimensional (2D) resistivity tomographies across two management systems (tillage/no tillage) replicated twice on each transect, using dipole‐dipole configuration and 0.25‐m inter‐electrode spacing. Soil texture, bulk density and water content were measured destructively. Greater average electrical resistivity (ER) was found in tilled plots, with maximum values of up to 1700 Ohm m. However, when the spatial correlation structure was considered in a mixed‐effects model, no significant difference in ER was found between tilled and untilled plots. Empirical semivariograms showed less spatial continuity and more noise in tilled plots. Resistivity was strongly correlated with rock fragment content (r = 0.68), with greater average values in ploughed plots, which may possibly be linked to kinetic sieving after ploughing. ERT was able to identify the position of gravel lenses and was also sensitive to the presence of clay (r = −0.45): a linear trend in resistivity across the field (r = 0.80) was consistent with a decreasing clay content (r = −0.68). Resistivity was correlated with rock fragments, clay and an interaction variable (water × rock fragments). There was a poor fit for the tilled plot where resistivity peaks could be linked to the presence of voids, but their detection would have required a resolution greater than that which we adopted.